IoT-Based Cooking Gas Leak Detection System - Zainal, Zainurul Syafikah; Masek, Alias (Research and Innovation in Technical and Vocational Education and Training, 2024)
The IoT-Based Cooking Gas Leak Detection System aims to warn users to avoid frequent fires due to gas leaks. The objective of this study is to design, develop, and test the functionality of a gas leak detection system. The prototype of the development of this system is based on the Design Thinking model. LCD display, buzzer, and blynk application can help users monitor and warn when gas leakage occurs. This gas detector uses an MQ-5 type gas detector to detect gas leakage readings in the percentage (%) that has been set in the software. The percentage of gas reading will be shown through the LCD display and blynk application while the buzzer will sound if there is a gas reading above 35%. A DC fan will suck in the leaking gas. At the same time, the solenoid valve will automatically close the hose. Arduino IDE software is used as software in this system. The implementation of this project involves testing using gas from a lighter. Expert verification has involved four experts consisting of lecturers and laboratory assistants from the Faculty of Technical and Vocational Education. As a result expert evaluation, shows that the development of a Cooking Gas Leak Detection System Using IOT has achieved the stated objective. Therefore, the development of this system is relevant to be developed to help users in detecting gas leaks.